Phytochemical content and antioxidant activity of Gynura procumbens in response to shade levels and rates of nitrogen fertilizer - Ahmed, Omar Ali; Mohammad Yusoff, Martini; Misran, Azizah; Megat Wahab, Puteri Edaroyati; Zentou, Hamid (Southern Cross Publishing, 2021)
Gynura procumbens is one of the most common medicinal plants with extensive pharmacological properties. Light intensity and nitrogenous fertilisers are two main limiting factors in primary and secondary metabolism in plants. Information on the effects of shade levels and nitrogenous fertiliser rates on phytochemical content and antioxidant activity of G. procumbens is much scarce. This justifies an in-depth study to determine the effects of phytochemical content and antioxidant activity. This study was conducted with four levels of shade (0, 30, 50, and 70%) and four nitrogen fertilizer rates (0, 100, 200 and 300 kg N ha−1). Data measurements were performed on protein content, C:N ratio, total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity (DPPH, FRAP) and flavonoid acids. The results showed that decreases in total phenol, flavonoid contents, C:N ratio and antioxidant activity were recorded with increasing shade levels and nitrogen rates. Protein content was increased with increases in shade levels and nitrogen fertilizer supplement. The highest flavonoid acids contents were observed from higher light intensity (no shade) and no nitrogen application. Enhancement in production of secondary metabolites and antioxidant activity were associated with high C:N ratio and low protein contents. The study demonstrated that high light intensity (0% shade) with a low N fertilizer rate (0 kg N ha−1) was suitable for both phenolic compounds and antioxidants activity. The present study suggested that G. procumbens can achieve higher production of polyphenolic compounds and antioxidant activity under low nitrogen availability and open field conditions.